SGLT2 Inhibitors Extra Glycemic Potential: A Possible Novel Approach to the Prevention of Atherosclerotic Events - Silumbwe Ceaser Wankumbu; Ji Xiao-Man; Siame Lukundo; Ming Xu (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Cardiovascular diseases are a major global health concern, with atherosclerosis being a significant contributor. Diabetes mellitus is a well-known risk factor for atherosclerosis, and SGLT2 inhibitors are more effective in reducing cardiovascular disease and mortality compared to other antihyperglycemic agents in patients with type 2 diabetes. Endothelial dysfunction, VSMC phenotypic alterations, inflammation, autophagy, oxidative stress, signaling hormones and dysbiosis are crucial factors and predictors of atherosclerosis and other cardiovascular events. SGLT2 inhibitors have been shown to alleviate these components in atherosclerotic models. Material and Methods: To proceed we analyzed and took into account all publications, including clinical trials, animal studies, in vitro observations, reviews, and meta-analyses from various scientific databases. Results: Evidently, SGLT2i attenuate the progression of atherosclerosis by repressing vascular inflammation, oxidative stress, endothelial dysfunction, mitigating vascular smooth muscle cells function, impairing foam cell formation, preventing platelet activation and restoration of normal autophagic function. Conclusion: Based on these findings, it can be inferred that SGLT2 inhibitors exhibit anti-atherosclerotic characteristics and may have positive implications for the management of atherosclerosis, particularly in individuals with diabetic complications.